Low doses of Bisphenol S affect post-translational modifications of sperm proteins in male mice - Řimnáčová, Hedvika; Štiavnická, Miriam; Moravec, Jiří; Chemek, Marouane; Kolinko, Yaroslav; García-Álvarez, Olga; Mouton, Peter R; Trejo, Azalia Mariel Carranza; Fenclová, Tereza; Eretová, Nikola; Hošek, Petr; Klein, Pavel; et al. (Reproductive biology and endocrinology, 2020)
BACKGROUND: Bisphenol S (BPS) is increasingly used as a replacement for bisphenol A in the manufacture of products containing polycarbonates and epoxy resins. However, further studies of BPS exposure are needed for the assessment of health risks to humans. In this study we assessed the potential harmfulness of low-dose BPS on reproduction in male mice. METHODS: To simulate human exposure under experimental conditions, 8-week-old outbred ICR male mice received 8 weeks of drinking water containing a broad range of BPS doses [0.001, 1.0, or 100 μg/kg body weight (bw)/day, BPS1-3] or vehicle control. Mice were sacrificed and testicular tissue taken for histological analysis and protein identification by nano-liquid chromatography/mass spectrometry (MS) and sperm collected for immunodetection of acetylated lysine and phosphorylated tyrosine followed by protein characterisation using matrix-assisted laser desorption ionisation time-of-flight MS (MALDI-TOF MS). RESULTS: The results indicate that compared to vehicle, 100 μg/kg/day exposure (BPS3) leads to 1) significant histopathology in testicular tissue; and, 2) higher levels of the histone protein γH2AX, a reliable marker of DNA damage. There were fewer mature spermatozoa in the germ layer in the experimental group treated with 1 μg/kg bw (BPS2). Finally, western blot and MALDI-TOF MS studies showed significant alterations in the sperm acetylome and phosphorylome in mice treated with the lowest exposure (0.001 μg/kg/day; BPS1), although the dose is several times lower than what has been published so far. CONCLUSIONS: In summary, this range of qualitative and quantitative findings in young male mice raise the possibility that very low doses of BPS may impair mammalian reproduction through epigenetic modifications of sperm proteins.
Keywords: Low dose effect; Dose-Response Relationship, Drug; DNA Damage; Phenols; vztah mezi dávkou a účinkem léčiva; epigeneze genetická; Endocrine disruptor; Phosphorylation; Post-translational modification; Epigenesis, Genetic; Sperm Maturation; poškození DNA; mužské pohlaví; posttranslační úpravy proteinů; sulfony; Bisphenol S; Mice; testis; endokrinní disruptory; fenoly; Sulfones; Endocrine Disruptors; Male reproduction; Protein Processing, Post-Translational; zvířata; zrání spermie; acetylace; myši; fosforylace; Acetylation; Spermatozoa; Testis; spermie; Male; Animals